The covid-19 in the Primary Health Care context (Research, Society and Development, 2021)
This article aims to develop a reflective theoretical study with an emphasis on the actions, challenges and recommendations of practices for the prevention, control and monitoring of PHC disease. The COVID-19 pandemic has been demanding a remodeling of structures, not only in hospital care, but, especially in interventions in communities and their social, urban and structural problems. The article highlights the work process and new technical and dynamic incorporations for prevention, surveillance and monitoring imposed by SARS-CoV2 on primary health care, which must also guarantee access to essential care. As it allows thinking about the most feasible forms of action, this article recognizes the principles of action in the health system, offering to managers and health professionals, through the interlocution between related studies, several measures that can help in assistance of pandemic. The COVID-19 pandemic changed the course of some health policies in the world. Patient-centered care requires a change in perspective towards a concept of community-centered care. As the primary health care is the first level of contact for individuals, family and community in a health system, constituting the preferred gateway to the care process, it is expected that the reflections raised by this article will contribute to an analysis that answers the main public health issues from the perspective of primary health care, preserving its stability, avoiding the disintegration of its actions and maintaining its functionality with the strengthening of local and community actions.